TO THE MATTER OF APPRAISAL OF TECHNICAL-ECONOMIC INDICES OF STEEL-MELTING FURNACES OF CONSTANT AND ALTERNATING CURRENT - Andrej I. Rozhkov; Anton I. Rozhkov (Литьë и металлургия)
It is shown that using of static thyristor compensation systems improves efficiency, decreases consumption of power and electrodes, but increases the cost of furnaces of alternating current.